Immunoglobulin Responses at the Mucosal Interface - Cerutti, Andrea (2011)
Mucosal surfaces are colonized by large communities of commensal bacteria and represent the primary site of entry for pathogenic agents. To prevent microbial intrusion, mucosal B cells release large amounts of immunoglobulin (Ig) molecules through multiple follicular and extrafollicular pathways. IgA is the most abundant antibody isotype in mucosal secretions and owes its success in frontline immunity to its ability to undergo transcytosis across epithelial cells. In addition to translocating IgA onto the mucosal surface, epithelial cells educate the mucosal immune system as to the composition of the local microbiota and instruct B cells to initiate IgA responses that generate immune protection while preserving immune homeostasis. Here we review recent advances in our understanding of the cellular interactions and signaling pathways governing IgA production at mucosal surfaces and discuss new findings on the regulation and function of mucosal IgD, the most enigmatic isotype of our mucosal antibody repertoire.